KBG syndrome complicated with chylothorax in a newborn: a case report and literature review - Wang, Yuqian; Peng, Xin; Zhu, Jing; Zou, Ning; Yu, Xiaotong; Yang, Liu (Frontiers in Pediatrics, 2025)
ObjectiveTo discuss a unique case of KBG syndrome (KBGS) in neonates that developed congenital chylothorax and to examine how ANKRD11 gene variations may be related to lymphatic malformation.MethodsThe newborn was delivered at 38+5 weeks of gestation, presenting with congenital chylothorax, a ventricular septal defect, feeding difficulties, and craniofacial dysmorphism, and has been diagnosed with KBGS. Whole exome sequencing (WES) was employed to validate the diagnosis of a genetic disorder. Also, a systematic literature search of published KBGS cases between 1975 and June 2025 (n = 246) was carried out.ResultsThe newborn was found to have a heterozygous ANKRD11 frameshift variant (NM_013275.6: c.37683769 del; p.His1256Glnfs *26), which came from his mother. The clinical presentation was congenital chylothorax, craniofacial dysmorphism (triangular face, bulging forehead, hypertelorism, short nose root, anteverted nostrils, big ears, and micrognathia), ventricular septal defect, and difficulty feeding. This was found to be the second case of KBGS with chylothorax in the literature review. The literature review revealed that the predominant universal neonatal phenotypes were feeding challenges (52.1%) and small-for-gestational-age status (41.1%). The long-term phenotypes included facial features (100%), macrodontia of upper central incisors (93.9%), skeletal disorders (90.7%), and developmental delay (93.2%). Other symptoms included short stature, neurological problems, and visual and auditory impairment. The incidence of skeletal developmental defects and developmental delay was considerably higher in truncated variant patients compared to missense variant patients (p < 0.05).ConclusionThe newborn presented with KBGS complicated by chylothorax, attributable to a pathogenic variant in the ANKRD11 gene. These results broaden the existing knowledge of KBGS clinical and genetic spectra. WES or whole-genome sequencing should be important in diagnosing patients with unexplained developmental abnormalities. It is imperative that the management for KBGS is multidisciplinary to deliver optimal prognosis and long-term outcomes.